Metaphor, nominalization, appraisal: analyzing coronavirus-related headlines and subheadings in China Daily and The Wall Street Journal - Luporini, Antonella (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper focuses on two corpora of headlines and subheadings from news articles about the coronavirus, published in China Daily (CD) and in The Wall Street Journal (WSJ) between January 7 and February 8, 2020. Applying Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and Systemic Functional Linguistics, particularly the nominalization framework (Halliday, 1997/2004) and Appraisal (Martin & White, 2005), the paper explores how the virus and actions taken against it are framed in the corpora through the use of metaphors, nominalizations, and evaluative language in general. Results highlight similarities in the metaphorical conceptualization of the virus/disease in the corpora, but also key differences in terms of framing. In China Daily, metaphor and nominalization function to frame the situation and the actions taken in mainly positive terms; conversely, in WSJ, the emerging outlook is predominantly pessimistic. The conclusive section takes stock of such differences, also in the light of the socio-cultural contexts in which they are embedded. Finally, remarks are made about the usefulness of the proposed theoretical and methodological approach, the main advantages being the holistic perspective on textual data emerging from the combination of metaphor and nominalization analysis – as the two phenomena often work synergistically – and systematicity brought about by integrating the appraisal framework into metaphor studies. At the textual and contextual level, the relevance of the findings lies in their contribution to a deeper understanding of different national responses, and their media representation, at the onset of the coronavirus crisis.